2018
DOI: 10.1093/arclin/acy085
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Emotional Processing in People with Symptomatic Huntington’s Disease: Impaired Emotion Regulation and Recognition of Emotional Body Language†

Abstract: Objective Emotion regulation and emotional body language (EBL) recognition represent two fundamental components of emotional processing that have recently seen a considerable surge in research interest, in part due to the role they play in optimizing mental health. This appears to be particularly true for clinical conditions that can profoundly affect emotional functioning. Among these is Huntington’s disease (HD), a neurodegenerative disorder that is associated with several psychological dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…In his seminal 1872 article On Chorea, George Huntington explained that "as the disease progresses, the mind becomes more or less impaired, in many amounting to insanity, while in others mind and body gradually fail until death relieves them of their sufferings" [1] (p. 320). Today, we know that what Dr Huntington called "insanity" translates into a number of significant psychological difficulties experienced by people with HD (pwHD), which most frequently include low mood and mood extremes, irritability and aggressiveness, anxiety, agitation, perseveration, compulsions, apathy, avoidance, emotion dysregulation, and increased risk of suicide [2][3][4][5][6][7][8][9][10]. More rarely, pwHD may also experience obsessive-compulsive behaviours, delusions, and hallucinations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In his seminal 1872 article On Chorea, George Huntington explained that "as the disease progresses, the mind becomes more or less impaired, in many amounting to insanity, while in others mind and body gradually fail until death relieves them of their sufferings" [1] (p. 320). Today, we know that what Dr Huntington called "insanity" translates into a number of significant psychological difficulties experienced by people with HD (pwHD), which most frequently include low mood and mood extremes, irritability and aggressiveness, anxiety, agitation, perseveration, compulsions, apathy, avoidance, emotion dysregulation, and increased risk of suicide [2][3][4][5][6][7][8][9][10]. More rarely, pwHD may also experience obsessive-compulsive behaviours, delusions, and hallucinations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the current literature around emotion regulation in the HD population is very limited [61]. In particular, the only two studies focusing on symptomatic individuals showed contrasting results [62,63], while the only study to date involving premanifest individuals reported no generalised difficulties of emotion regulation, but a potential predictive role of subclinical depressive symptoms over deficits of specific emotion regulation components [64]. Nonetheless, considering a potential early onset of the wellestablished emotion recognition deficits found in HD's symptomatic stage [65], as well the reports from families of premanifest individuals suggesting problems congruent with emotional regulation difficulties [4], it is encouraging that mindfulness could be beneficial in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This may be implemented by way of interventions focused on the development of emotion regulation strategies, and especially cognitive reappraisal (Buhle et al ., ; Gross, ). Indeed, reports from previous quantitative and qualitative investigations suggest that individuals living with long‐term neurological conditions including MND can benefit greatly from successful emotion regulation (Williams, Howlett, Levita, & Reuber, ; Williams, Levita, & Reuber, ; Zarotti, Fletcher, & Simpson, ; Zarotti, Simpson, Fletcher, Squitieri, & Migliore, ; Zarotti et al ., ). In addition, HCPs may be able to provide practical suggestions to mitigate the impact on MND on the mealtime experience, such as the use of adapted cutlery and providing advice on tailoring portions around specific mealtime needs (e.g., need for greater time).…”
Section: Discussionmentioning
confidence: 99%